2016
DOI: 10.1007/s00276-016-1690-1
|View full text |Cite
|
Sign up to set email alerts
|

Anterior loop of the mental nerve, mental foramen and incisive nerve emergency: tridimensional assessment and surgical applications

Abstract: Prevalence, location and length of the anterior loop can be overlooked if only two-dimensional pre-surgical studies are performed. Therefore, three-dimensional imaging and modeling of anatomic structures should be used for the pre-operative examination of the interforaminal area. Given the wide variability of the emergency pattern of the mental nerve and the prevalence and location of the anterior loop, it should be studied in every patient individually.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 29 publications
0
10
1
1
Order By: Relevance
“…Measurements made on cross sections do not get an optimal result because two-dimensional slices are subjected to interpretation efficiency of the operators. On the other hand it was argued that, determining the length of the loop through panoramic views from CBCT scans with high thickness is similar to researches using panoramic radiographs (12,(35)(36)(37)(38).…”
Section: Discussionmentioning
confidence: 74%
“…Measurements made on cross sections do not get an optimal result because two-dimensional slices are subjected to interpretation efficiency of the operators. On the other hand it was argued that, determining the length of the loop through panoramic views from CBCT scans with high thickness is similar to researches using panoramic radiographs (12,(35)(36)(37)(38).…”
Section: Discussionmentioning
confidence: 74%
“…With the intention of improving the biomechanics of the prosthesis, reducing the distance from the distal cantilever, in many cases, the implants are installed close to the mental foramen exit, not taking into account the presence of the AL (Prados-Frutos et al, 2017). Velasco-Torre et al ( 2017) report in their study that 37% of the patients who had implants installed in the intraforaminal region had sensory changes, and 10 to 15% of these changes were permanent, justifying the relevance of studying the anatomical variations of this region (Wismeijer et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…12-14 In contrast, other studies found a low prevalence of the loop from 7% to 53.7%. 15, 16 The possible reason for this might be different methods of CBCT assessment. Each method has difficulty in determining the most anterior point of the loop; however, transverse oblique method makes the assessment reliable as multiple anatomical structures can be displayed in the same view.…”
Section: Discussionmentioning
confidence: 99%